HIGH PREVALENCE OF SUBSTANTIAL SHOULDER PROBLEMS AMONG ELITE ADOLESCENT HANDBALL PLAYERS: THE KAROLINSKA HANDBALL STUDY. Issue 4 (1st February 2017) - Asker, Martin; Holm, Lena W; Källberg, Henrik; Waldén, Markus; Skillgate, Eva
Abstract : Background: Recent studies report a high prevalence of shoulder problems in senior team handball players but studies in adolescent players are lacking. Objective: To measure the season prevalence of substantial shoulder problems (SSP) in elite adolescent handball players. Design: Longitudinal cohort study with weekly online follow-ups. Setting: Elite adolescent male and female handball players at handball-profiled high schools in Sweden. Participants: 471 (54% females, mean age 16) were recruited from 10 of 15 national handball-profiled high schools. Assessment of Risk Factors: The prevalence of SSP, stratified by age, was assessed through repeated online questionnaire data. Main Outcome Measurements: Season prevalence of SSP during the previous handball season was measured during the pre-season (baseline), and was studied prospectively during the current season via weekly reports using the OSTRC Overuse Injury Questionnaire. SSP was defined as problems leading to moderate or severe reductions in handball participation or performance, or to time-loss. Results: The weekly response rate was 86–96% and 83% of the players responded to at least 90% of the weekly reports. The previous season prevalence measured at baseline was 8% (95% CI 5–11%) among players in the 1st grade and 20% (95% CI (15–26%) in the 2nd and 3rd grades. During the prospective season, 22% (95% CI 17–27%) of players in the 1st grade reported having SSP, and 27% of players in the 2nd and 3rd grades. Of those with SSP at some point during the previous season, 67% (95% CI 54–77%) also reported SSP at least once during the prospective season. Conclusions: The season prevalence of SSP is high among adolescent handball players and the prevalence increases when the players start high school. A majority of players with previous SSP also report subsequent SSP problems indicating that the pre-high school period is where prevention strategies preferably should be implemented.